Understanding farmers' motivations for providing unsubsidised environmental benefits. (July 2018) - Mills, Jane; Gaskell, Peter; Ingram, Julie; Chaplin, Stephen
Highlights: Farmers' extrinsic and intrinsic motivations for undertaking unsubsidised environmental practices is investigated. Around 25% of environmental activity on arable farms in England were found to be unsubsidised. Agronomic and environmental reasons dominated motivations for engaging in unsubsidised activity. Findings can inform message framing to encourage voluntary environmental behaviour. Abstract: This paper examines farmers' motivations for voluntary unsubsidised practices that benefit the environment. It identifies amongst a group of English farmers the amount of unsubsidised environmental activities on mainly arable land, and explores the extent to which motivations are extrinsic and intrinsic for undertaking this unsubsidised activity. Using responses from a national survey in England of 1, 345 farmers, in-depth face-to-face interviews with 60 farmers and an analysis of existing agri-environment scheme data, the extent to which subsidised and unsubsidised environmental activity is undertaken on arable land was identified. Furthermore, it was also possible to identify and compare the motivations behind subsidised and unsubsidised environmental activity and to understand the interaction between these two types of activity at the farm scale. The research found that around 25% of all environmental activity undertaken on arable farms in England is unsubsidised, although some of this activity sits alongside subsidised activity. There were clear differences between the motivations for undertaking subsidised and unsubsidised environmental activities. Financial reasons dominated farmers' motivations for engaging in subsidised agri-environment scheme practices, whilst agronomic and environmental motivations were of greater importance for unsubsidised activity. Data analysis also revealed over-subscription in agri-environment schemes, with a considerable amount of environmental activity occurring without payment. From a policy perspective it is helpful to understand motivations for existing unsubsidised environmental activity as this can inform the design of advice and message framing to encourage uptake of more widespread voluntary environmental behaviour.